2022
DOI: 10.1063/5.0099151
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and pore structure of basalt–polypropylene fiber fly ash concrete exposed to high temperatures

Abstract: The deterioration of concrete structures after fires has been widely concerned. The purpose of this paper is to study the influence of high temperature on the mechanical properties and pore structure of hybrid basalt–polypropylene fiber fly ash concrete. The mechanical properties and damage amount of hybrid basalt–polypropylene fiber concrete with different content of fly ash (FA0, FA10, FA20, and FA30) at different temperatures (20, 200, 400, 600, and 800 °C) were investigated. Additionally, the pore structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Compared to the control concrete containing 100% recycled aggregates and without basalt fibers, 1% basalt fibers resulted in a 31.6% decreasing in drying shrinkage (Jiao et al, 2022). The results demonstrated that hybrid basalt-polypropylene fiber-reinforced concrete outperformed conventional concrete (Zhang, 2017;Zhang et al, 2018;Sun et al, 2019;Fu et al, 2021;Klyuev et al, 2023).…”
Section: Introductionmentioning
confidence: 90%
“…Compared to the control concrete containing 100% recycled aggregates and without basalt fibers, 1% basalt fibers resulted in a 31.6% decreasing in drying shrinkage (Jiao et al, 2022). The results demonstrated that hybrid basalt-polypropylene fiber-reinforced concrete outperformed conventional concrete (Zhang, 2017;Zhang et al, 2018;Sun et al, 2019;Fu et al, 2021;Klyuev et al, 2023).…”
Section: Introductionmentioning
confidence: 90%